Predicting mental health based on religious beliefs and social intelligence in Payame Noor university students - Shahande, Amene (Researcher Bulletin of Medical Sciences, 2021)
Objective: Students in terms of the importance and direct impact they have on the growth, development and progress of society are considered as efficient and specialized forces of the future for society and due to the special conditions of the student period such as being away from family, entering a large and stressful complex. Economic problems, high volume of courses and intense competition require more mental health. Religion, as one of the spiritual and psychological aspects of human beings, is one of the important and special issues and examining its effects can help human beings in terms of mental health. It seems that there is a relationship between mental health and religious beliefs and social intelligence in students. In this regard, the purpose of this study is to investigate the role of religious beliefs and social intelligence in predicting the mental health of students at Payame Noor Khoy University. Materials and Methods: The present study was descriptive and performed through multivariate regression and Pearson correlation. For this purpose, from the statistical population of undergraduate students in Payame Noor Khoy University with the help of Fidell & Tabachnick formulas, a sample of 120 people (60 girls and 60 boys) selected by random cluster sampling in the academic year 2016-2017. From the questionnaire, 28 questions of Goldberg mental health question, 25 questions of Braheni religious attitude and 21 questions of Tromso social intelligence were completed by the subjects and the results were analyzed using SPSS statistical program version 23. Results: Out of 120 students, in this study, the highest number of students belonged to the group of 20-25 years old, 78.3% and the highest number of students belonged to technical students. Findings show that there is a significant relationship between religious beliefs and mental health, as well as social intelligence and mental health. R = 0.71), p <0.01 (Pearson correlation analysis shows that according to the sample number of 120 people and coefficient There is a direct and significant relationship between mental health and religious beliefs (0.74) and there is a direct and significant relationship between mental health and social intelligence based on the correlation coefficient (0.76). Conclusion: The results showed that there is a significant relationship between religious beliefs and mental health and social intelligence of Payame Noor Khoy University students. This means that the more positive religious beliefs people have, the better their mental health, and the higher their social intelligence, the better their mental health.